Caracterização morfológica da corrosão por pite da liga AL2024 em soluções contendo cloretos e molibdatos - De Jesus Silva, José Wilson [UNESP]; Codaro, Eduardo Norberto [UNESP]; Nakazato, Roberta Zenhei [UNESP]; De Oliveira Hein, Luiz Rogério [UNESP] (My University, 2003)
A very new method application for digital image processing and analysis to classify shape and evaluate size and morphology parameters of pit corrosion is used in this paper. This method seems to be very effective to analysis surfaces with low or high degree of pitting formation. Pits formed on 2024 alloy surface by chloride and by chloride + molibdate anions have similar mean area, are found to be widther than deeper and exhibit predominantly conical or near-conical and irregular geometries.
Morphologic characterization of pitting corrosion of 2024 alloy in containg-chlorides and molibdates solutions
Keywords: Digital image processing; Morphology characterization; Pitting corrosion; Chlorine compounds; Image processing; Morphology; Negative ions; Pitting